Airpower in the Union of South Africa’s First World War campaign in German South West Africa (Historia, 2021)
During the Great War, aircraft were used primarily for reconnaissance and artillery spotting. The Union of South Africa’s First World War campaign in German South West Africa (GSWA) allowed for South Africa’s first employment of military aeroplanes in conventional warfare. The creation and employment of the South African Aviation Corps (SAAC) within the Union Defence Force (UDF) provided ground forces with a substantial force multiplier in terms of forward reconnaissance. The aerial reconnaissance allowed General Louis Botha and his subordinate commanders to gain a better understanding of the tactical picture and facilitated the battle concept. This paper discusses the role and impact of aerial operations during the GSWA campaign. The campaign was characterised by sweeping envelopments which were executed by the Union’s commandos. During the latter part of the campaign aeroplanes provided the UDF with intelligence in terms of the location and concentration of German forces, which assisted in their final encirclement.
Keywords: German South West African campaign; Union Defence Force; airpower; First World War